The Storia della Biblioteca Berio of Luigi Marchini: reflections about the recent printed edition - Francesca Nepori; Graziano Ruffini; Valentina Sonzini (Bibliothecae.it)
As part of the events celebrating its bicentenary, the Biblioteca Civica Berio has published Luigi Marchini’s volume on the history of the institution. The unpublished work offers a detailed narrative from the birth of the Berio collection in the eighteenth century to the Second World War, with an appendix edited by Laura Malfatto to complete the contemporary history of the institution. The article summarises the introductory speeches given at the presentation of the volume on 22 May, focusing on the author - a bibliophile and bibliographer - and the importance of the work for the history of libraries in general.